2017
DOI: 10.1007/978-3-319-62597-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technology in Mathematics Education: Research over the Last Decade

Abstract: In this survey paper we focus on identifying recent advances in research on digital technology in the field of mathematics education. We have used Internet search engines with keywords related to mathematics education and digital technology and have reviewed some of the main international journals. We identify five sub-areas of research, important trends of development, and illustrate them using case studies: mobile technologies, massive open online courses (MOOCs), digital libraries and designing learning obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…There are different kinds of e-learning activities. There are e-learning activities in which materials are provided for self-education (e.g., [6]) and also e-learning activities in virtual spaces able to host collaborative learning communities, organized in real learning groups, or in communities of practice [7], where each member increases their knowledge and skills by building them with the rest of the group, based on the cognitive problems typical of a given profession (e.g., [8,9]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There are different kinds of e-learning activities. There are e-learning activities in which materials are provided for self-education (e.g., [6]) and also e-learning activities in virtual spaces able to host collaborative learning communities, organized in real learning groups, or in communities of practice [7], where each member increases their knowledge and skills by building them with the rest of the group, based on the cognitive problems typical of a given profession (e.g., [8,9]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Three major issues debated nowadays in mathematics education (in addition to alternative views on pre-college curricula mentioned in Section 2) concern mathematical knowledge for teaching [50,51], the relationship between conceptual and procedural knowledge [52,53] and the use of digital technology [54,55]. This paper, written as the author's reflection on the use of Wolfram Alpha with elementary teacher candidates that found it conducive in uplifting their conceptual understanding of mathematics and in fostering skills in numeric and symbolic computations, contributes to this debate.…”
Section: Discussionmentioning
confidence: 99%
“…Research is being conducted to look at the effectiveness of the technology and teaching approaches that have been innovated and modified to meet the curriculum needs and to achieve the goal of improving student competency. As the findings of studied by Radovic, Maric & Passey [35], Eyyam & Yaratan [15], Clarebout et al [10], Gurbin [21], Smith, Shin, Kim & Zawodniak [41] and Borba et al [5], have reported that the results of the technology integration and improvement of traditional approach has influenced and had a significant impact on student achievement. According to Mistretta [28], Mat Sina, Talib & Norishaha [26], Brakoniecki, Amador & Glassmeyer [6] and Gurbin [21], most technology products are widely applied and used in learning, such as gadgets like tabs and smartphones, learning aids likes graphic-scientific calculators, web-based, apps, internet-based and more.…”
Section: Introductionmentioning
confidence: 93%